THE MAPPING OF ACTION VERBS IN THE TEACHING OF ENGLISH FOR FOOD PRODUCTION - Paramita, Putu Dian Yuliani; Kuntariati, Utik (Jurnal Manajemen Pelayanan Hotel, 2019)
This study is focused on the procedure of verbsâ€™ translation in English (source language) into Indonesian language (target language), and how the mapping of action verb meanings in the procedural text. The research uses qualitative method, employing a cooking book recipe â€œStep by Step Cooking Balinese Delightful for Everydayâ€ as its data source and its Indonesian translation. The theory used in this research is the theory of Vinay and Darbelnet (in Venuti, 2000) about translation procedures that include borrowing, calque, literal translation, transposition, modulation, equivalence, and adaptation. The theory of applying the natural semantic metalanguage approach (NSM) proposed by Wierzbicka (1996) is used to discuss the mapping of English action verbs. The theory is applied in order to explain how the Indonesian action verb meanings are mapped into English, with the exponential mapping technique. The description of the mapping meanings including the exponential mapping to the action verb of the Indonesian language has produced a new dimension. This new dimension turns out to be able to explore the meaning of the lexical item including the one that has even a subtle difference, therefore there is no more swirling of meaning. Keywords: translation procedure, action verb, mapping of meaning